Thomist Advice to Christian Philosophers - Di Ceglie, Roberto (European Journal for Philosophy of Religion, 2021)
In Advice to Christian philosophers (1984) Alvin Plantinga suggested that Christians who propose to be philosophers should not limit themselves to being philosophers who happen, incidentally, to be Christians. Instead, they should develop a Christian philosophy. From this, however, a problem followed, which is still seen as a reason to deny that a Christian philosophy is possible. It seems implausible that the outcome of the interaction between faith and philosophy is, really, philosophy and not merely theology. Plantinga did not deal with this problem. Unlike him, thinkers of various orientations, especially scholars of Thomas Aquinas, had discussed it during the French querelle in the 1930s. In this article, I argue that they did not solve this problem because they did not examine the relationship between faith and philosophy by considering what faith requires in order to relate to reason. Instead, this consideration was suggested by Plantinga’s Advice and, long before, it had been developed in detail by Thomas Aquinas. It is, therefore, time to propose Thomist Advice to Christian Philosophers.